Proyecto de factibilidad para la creación de una microempresa productora y comercializadora de café de higo con filtrantes, ubicada en el cantón Cayambe, provincia de Pichincha. - Sánchez Monteros, Diego Mauricio (2014)
The progressive growth of the coffee sector is an economic and social reality in our country, however, the need to improve the product on the market haven’t been satisfied. For this situation, this project was created to meet those needs through the a innovation product; the most important is the product quality, practicality and speed in use, with this form people can enjoy the exquisite flavor of natural cup of coffee; and we can take care their health. For the target market of the product, we have been considered the ―Canton Cayambe‖, because, it is agricultural and in the last years we can note the advanced development and growth experienced. In the market study, we have a lot of unsatisfied demand. This situation shows us the potential to exploit the market, and then we can affirm our success.